Effect of chitosan grafted polyethylenimine nanoparticles as a gene carrier on mesenchymal stem cells viability - Malakooty poor, Elham; Baghaban Eslaminejad, Mohamadreza; Bagheri, Fatemeh; Mollarazi, Esmail; Gheibi, Nematollah (Archives of Advances in Biosciences, 2013)
This study discusses the effect of complexes of chitosan grafted polyethylenimine(Ch-PEI) with plasmid DNA on viability of mesenchymal stem cells(MSCs) derived from human marrow. Ch-PEI/pDNA nanoparticles were synthesized through the complex coacervation method using pIRES plasmid containing Green Fluorescent Protein (GFP) gene. To confirm the complexation, samples were run through an agarose gel. Human bone marrow mesenchymal stem cells were studied for the cytotoxicity of the nanoparticles by MTT assay. MTT results indicated Ch-PEI does not have any significant cytotoxicity compared with PEI and Lipofectamine2000 leading to 40% cytotoxicity. According to the results it seems that grafting chitosan with PEI improves the MSCs viability.